Where’s the Spin? A DFT Study of Mixed-Valence Cyanide-Bridged Ruthenium Polypyridines - Pieslinger, German Eduardo (2020)
This article discusses the use of density functional theory (DFT) calculations in classifying and characterizing bimetallic ruthenium mixed-valence systems in terms of their electronic localization/ delocalization degree. A standard B3LYP/LanL2DZ methodology including integral equation formalism-polarizable continuum model (IEF-PCM) solvent model is evaluated for a set of 16 nonsymmetric mixed-valence cyanide-bridged ruthenium polypyridines. This procedure reproduces well the features of the observed electronic and vibrational spectra, with better agreement for the more delocalized systems, and therefore provides an appropriate description of the electronic structures. Computed spin densities support class II or class III Robin-Day assignments and allow to quantify the electronic delocalization degree. The applied methodology yields good results due to the nature of the systems explored, which display a strong electronic coupling promoted by the cyanide-bridge and a lack of strong specific solvation effects. This procedure is not only useful in the study of ground state mixed-valence systems, but also provides a powerful insight into photoinduced mixed-valence excited states of related complexes.